The growth inhibitory potential and antimetastatic effect of camel urine on breast cancer cells in vitro and in vivo - Romli, Muhammad Firdaus; Abu, Nadiah; AbdulRahman Khorshid, Faten; Syed Najmuddin, Syed Umar Faruq; Yeap, Swee Keong; Mohamad, Nurul Elyani; Hamid, Muhajir; Mohammed Alitheen, Noorjahan Banu; Nik Abdul Rahman, Nik Mohd Afizan (SAGE Journals, 2017)
Although it may sound unpleasant, camel urine has been consumed extensively for years in the Middle East as it is believed to be able to treat a wide range of diseases such as fever, cold, or even cancer. People usually take it by mixing small drops with camel milk or take it directly. The project aims to study the effects of camel urine in inhibiting the growth potential and metastatic ability of 4T1 cancer cell line in vitro and in vivo. Based on the MTT result, the cytotoxicity of camel urine against 4T1 cell was established, and it was dose-dependent. Additionally, the antimetastatic potential of camel urine was tested by running several assays such as scratch assay, migration and invasion assay, and mouse aortic ring assay with promising results in the ability of camel urine to inhibit metastatic process of the 4T1 cells. In order to fully establish camel urine’s potential, an in vivo study was carried out by treating mice inoculated with 4T1 cells with 2 different doses of camel urine. By the end of the treatment period, the tumor in both treated groups had reduced in size as compared to the control group. Additional assays such as the TUNEL assay, immunophenotyping, cytokine level detection assay, clonogenic assay, and proteome profiler demonstrated the capability of camel urine to reduce and inhibit the metastatic potential of 4T1 cells in vivo. To sum up, further study of anticancer properties of camel urine is justified, as evidenced through the in vitro and in vivo studies carried out. Better results were obtained at higher concentration of camel urine used in vivo. Apart from that, this project has laid out the mechanisms employed by the substance to inhibit the growth and the metastatic process of the 4T1 cell.